Technology is changing lending: Implications for research - Sutherland, Andrew G. (Journal of Accounting and Economics, 2020)
Costello, Down, and Mehta (2020) trace their slider intervention to deviations from the credit line amount recommended by a credit scoring model. The deviations are followed by larger delinquency declines and bigger sales orders, and Costello et al. interpret these results using discretion-based theories. However, incremental deviations are concentrated on newer clients rather than those the lender has accumulated soft information about. Deviations also appear larger for public than private borrowers. My discussion evaluates whether these results align with discretion-based theories, and explores alternative interpretations based on salience and unique aspects of the trade credit setting. Differences in interpretation aside, the evidence is informative about technological advances in commercial lending. I conclude with an overview of several recent advances and discuss the implications for lending research.